THINKING OF PEACE, DEMOCRACY AND POLITICS OF INSULTS IN GHANA: THE PARADOX OF FREEDOM AND CULTURE OF VIOLENCE - Samuel Marfo (European Scientific Journal, ESJ, 2013)
Ghana is perceived as a peaceful country in a volatile region and prides itself of becoming a middle-income country in a foreseeable future. Considering the political climate of Ghana as opposed to other countries in the West Africa-sub region including Nigeria, Cote d’Ivoire, Liberia and Sierra Leone among others, Ghana can be said to be a ‘small heaven’ in a conflict endemic sub-continent. Having experienced most coup d’états and political summersaults after independence in 1957, Ghana is now a democratic country and regulated by the Republican Constitution of 1992. The liberalization of the airwaves, coupled with the practice of multi-party democracy, has given the citizenry the opportunity and freedom of speech and freedom of association. However, a critical observation and monitoring of the events in Ghana in recent times have revealed that, due to freedom of speech, the political landscape of the country has become a theater of most vitriolic insults especially from politicians and their cronies which poses threat to the democratic peace enjoined in the country. The position of this paper is that unless pragmatic and concrete efforts are made to transform the political landscape of Ghana, the democratic freedom of the people will gradually but steadily trap the country to a state of insecurity.